3D printed polylactic acid nanocomposite scaffolds for tissue engineering applications. (January 2020) - Alam, Fahad; Varadarajan, K.M.; Kumar, S.
Abstract: In this study, biodegradable polylactic acid (PLA) and PLA nanocomposite scaffolds reinforced with magnetic and conductive fillers, were processed via fused filament fabrication additive manufacturing and their bioactivity and biodegradation characteristics were examined. Porous 3D architectures with 50% bulk porosity were 3D printed, and their physicochemical properties were evaluated. Thermal analysis confirmed the presence of ~18 wt% of carbon nanostructures (CNF and GNP; nowonwards CNF) and ~37 wt% of magnetic iron oxide (Fe2 O3 ) particles in the filaments. The in vitro degradation tests of scaffolds showed porous and fractured struts after 2 and 4 weeks of immersion in DMEM respectively, although a negligible weight loss is observed. Greater extent of degradation is observed in PLA with magnetic fillers followed by PLA with conductive fillers and neat PLA. In vitro bioactivity study of scaffolds indicate enhancement from ~2.9% (PLA) to ~5.32% (PLA/CNF) and ~ 3.12% (PLA/Fe2 O3 ). Stiffness calculated from the compression tests showed decrease from ~680 MPa (PLA) to 533 MPa and 425 MPa for PLA/CNF and PLA/Fe2 O3 respectively. Enhanced bioactivity and faster biodegradation response of PLA nanocomposites with conductive fillers make them a potential candidate for tissue engineering applications such as scaffold bone replacement and regeneration. Graphical abstract: Image 1 Highlights: PLA nanocomposites scaffolds filled with carbon structures (CNF) and iron oxide (Fe2 O3 ) particles were fabricated by FFF. In vitro bioactivity study of scaffolds indicate enhancement from ~2.9% (PLA) to ~5.32% (PLA/CNF) and ~ 3.12% (PLA/Fe2 O3 ). Both the fillers improve the wettability and thus, bioactivity, water absorbtion capacity and biodegradation response. Stiffness obtained from the compression tests showed decrease from ~680 MPa (PLA) to 533 (PLA/CNF) and 425 (PLA/Fe2 O3 ) MPa. While PLA/CNF shows promise in terms of improved bioactivity, further work is needed to address printing challenges.